DAMPAK TUNJANGAN PROFESI (SERTIFIKASI GURU) DALAM OPTIMALISASI KINERJA KEPALA SEKOLAH DASAR KECAMATAN SAMARINDA ULU - Wuryanti . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The purpose of this article is to explain the impact of professional allowance to optimization work of Headmaster of elemantary school in Samarinda Ulu. The result known that Headmaster performance getting better after releasing the allowance policy. Work performance’s indicators of headmaster can be traced from supervision activity toward learning-teaching process, briefing, guiding, giving an opportunity extended study, financial management, enhancement of providing school infrastructure adopting the need and priority.